2009
DOI: 10.1016/j.cell.2008.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Transport of Amino Acids Regulates mTOR and Autophagy

Abstract: SUMMARY Amino acids are required for activation of the mammalian target of rapamycin (mTOR) kinase which regulates protein translation, cell growth, and autophagy. Cell surface transporters that allow amino acids to enter the cell and signal to mTOR are unknown. We show that cellular uptake of L-glutamine and its subsequent rapid efflux in the presence of essential amino acids (EAA) is the rate-limiting step that activates mTOR. L-glutamine uptake is regulated by SLC1A5 and loss of SLC1A5 function inhibits cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
1,470
6
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,531 publications
(1,598 citation statements)
references
References 57 publications
69
1,470
6
15
Order By: Relevance
“…23 Among those 6 transporters, the bi-directional transporters LAT-1 and LAT-2 export nonessential glutamine to enable the uptake of essential amino acids, which in turn activate the mammalian target of the rapamycin pathway promoting cell growth and survival. 31 Although biologically active small molecules against CD98-associated light chains have been identified, anti-CD98 antibodies provide another approach to modifying amino acid transport. 5,[11][12][13] Our data demonstrate for the first time that CD98 is overexpressed in CD34 1 -primary AML cells and in the squamous cell carcinoma subtype of NSCLC (Supporting Information Figs.…”
Section: Discussionmentioning
confidence: 99%
“…23 Among those 6 transporters, the bi-directional transporters LAT-1 and LAT-2 export nonessential glutamine to enable the uptake of essential amino acids, which in turn activate the mammalian target of the rapamycin pathway promoting cell growth and survival. 31 Although biologically active small molecules against CD98-associated light chains have been identified, anti-CD98 antibodies provide another approach to modifying amino acid transport. 5,[11][12][13] Our data demonstrate for the first time that CD98 is overexpressed in CD34 1 -primary AML cells and in the squamous cell carcinoma subtype of NSCLC (Supporting Information Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle growth is regulated primarily by the mammalian target of rapamycin complex 1 (mTORC1) signaling pathway, which enhances the capacity for mRNA translation and reduces flux through catabolic pathways such as the autophagy‐lysosome and the ubiquitin proteasome system (Nicklin et al, 2009). mTORC1 signaling has consistently shown to be activated in response to both muscle loading (e.g., resistance exercise), and amino acid consumption/treatment (Marcotte, West, & Baar, 2015), and as such these stimuli represent excellent candidates as therapies for attenuating the muscle wasting associated with a number of disease states and ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Early evidence has suggested that the uptake of exogenous L-glutamine and its efflux out cells serves to maintain intracellular levels of essential amino acids (EAA) such as leucine, leading to the activation of the mTOR-S6K1 pathway. These findings provide further evidence that L-glutamine directly impacts on upstream mTORC1, leading to EAA exchange to regulate cell growth and proliferation [29]. Interestingly, intracellular levels of glutamine and leucine support glutaminolysis, promoting lysosomal translocation and mTOR activation [82].…”
Section: Energy Addiction Growth and Proliferationmentioning
confidence: 66%
“…The main member of the ASC family of transporters, also known as solute linked carrier family 1 member A5 (SLC1A5), acts as a high affinity transporter of glutamine, and it has been shown to be upregulated in a diverse panel of cultured human cancer cell lines [26][27][28]. Further analysis showed that the inhibition of SLC1A5 decreased uptake of L-glutamine, inhibited the mammalian target of rapamycin (mTOR), triggered autophagy, and cell death [29,30]. After its uptake, glutamine catabolism begins with an initial deamination converting glutamine to glutamate, in a reaction catalyzed by a phosphate-dependent glutaminase (GLS1 and GLS2).…”
Section: Glutamine Metabolismmentioning
confidence: 99%
See 1 more Smart Citation